2022
DOI: 10.3201/eid2810.220391
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Socioeconomic Factors Associated with Fungal Infection Risk, United States, 2019

Abstract: In support of improving patient care, this activity has been planned and implemented by Medscape, LLC and Emerging Infectious Diseases. Medscape, LLC is jointly accredited by the Accreditation Council for Continuing Medical Education (ACCME), the Accreditation Council for Pharmacy Education (ACPE), and the American Nurses Credentialing Center (ANCC), to provide continuing education for the healthcare team. Medscape, LLC designates this Journal-based CME activity for a maximum of 1.00 AMA PRA Category 1 Credit(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Various studies have compared the gender prevalence of fungal infections in different populations; however, the majority of the studies are from the United States [ 17 , 18 ]. The results of the present study showed an increase in the prevalence of fungal infections in the female population (53.68%) compared to males (46.32%).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have compared the gender prevalence of fungal infections in different populations; however, the majority of the studies are from the United States [ 17 , 18 ]. The results of the present study showed an increase in the prevalence of fungal infections in the female population (53.68%) compared to males (46.32%).…”
Section: Discussionmentioning
confidence: 99%
“…Lower socioeconomic status may be associated with higher levels of mold in the home 11 as well as with certain underlying medical conditions that increase the risk for fungal infections. 12 Further studies accounting for the critical role of health disparities in post-disaster health effects of mold are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other studies have reported an association between male sex and increased risk of IC [ 27 , 28 ]. While we do not expect that sex-specific behaviors or exposures should play a role in early post-transplant IC, sex-related variability in immunologic response to fungi may.…”
Section: Discussionmentioning
confidence: 99%